Teacher training and geographical education: autonomous field research seeking identify geomorphological risks - Afonso, Anice Esteves; Silva, Luiz Felipe Hygino Sampaio da; Costa, Débora Guerreiro da (Geosaberes; Vol 10 No 22 (2019): Sept - Dec, 2019)
The current LDB9394 suggests the dissemination of natural disaster prevention mechanisms at all levels of education. The DGEO/FFP/UERJ seeks to train teachers capable of producing methodologies that insert this theme in basic geographic education. The students are oriented to study situations of natural disasters in the RMRJ (where they will probably act as teachers), doing autonomous researches (according to previous orientation) in different neighbourhoods, seeking to understand relations between natural processes and local socio-environmental dynamics. The teaching materials produced (risk prevention booklets, games, workshops, etc.) can be adapted to schools in different locations with similar natural risks, consolidating the educational practice that leads to societies more resilient to disasters caused by extreme natural events.